Analyzing and evaluating the content of grammatical rules according to the functional approach in series of Al- Arabiyah Bain Yadaik Text Book 3 - Hashem, Gamal Ahmed Fouad Abdelkarim (Tanjong Malim, 2022)
Analyzing and evaluating the content of grammatical rules according to the functional approach in series of Al- Arabiyah Bain Yadaik Text Book 3 by Hashem, Gamal Ahmed Fouad Abdelkarim